2013
DOI: 10.1371/journal.pone.0064320
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Color Quantum Dot Tracking Using a High-Speed Hyperspectral Line-Scanning Microscope

Abstract: Many cellular signaling processes are initiated by dimerization or oligomerization of membrane proteins. However, since the spatial scale of these interactions is below the diffraction limit of the light microscope, the dynamics of these interactions have been difficult to study on living cells. We have developed a novel high-speed hyperspectral microscope (HSM) to perform single particle tracking of up to 8 spectrally distinct species of quantum dots (QDs) at 27 frames per second. The distinct emission spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 52 publications
(66 reference statements)
1
99
1
Order By: Relevance
“…In contrast to that, in our previous study, we found dimerization to be independent of receptor expression levels in the range from 20,000 to 260,000 copies per cell (19). According to single particle tracking studies of EGFR, the receptor forms transient dimers in the absence of EGF (20)(21)(22); on the other hand, results of Tao and Maruyama (23) indicate that EGFR dimers are already formed in the endoplasmic reticulum, which would suggest a much more stable association. Among possible explanations of the contradictory findings are the intrinsic differences between cell lines as well as differences in the state of the cells used in the individual studies.…”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to that, in our previous study, we found dimerization to be independent of receptor expression levels in the range from 20,000 to 260,000 copies per cell (19). According to single particle tracking studies of EGFR, the receptor forms transient dimers in the absence of EGF (20)(21)(22); on the other hand, results of Tao and Maruyama (23) indicate that EGFR dimers are already formed in the endoplasmic reticulum, which would suggest a much more stable association. Among possible explanations of the contradictory findings are the intrinsic differences between cell lines as well as differences in the state of the cells used in the individual studies.…”
Section: Introductioncontrasting
confidence: 99%
“…a nonconstant diffusion coefficient, which causes the nonergodic behavior. Recent measurements reporting on the variation of diffusion coefficient in space or time [10][11][12], sometimes associated with anomalous and nonergodic diffusion [7], justify these assumptions phenomenologically. However, some questions remain unanswered: What causes such kinetic heterogeneity at the microscopic level?…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the surface modification of QDs with the listed affinity tags and biomolecules (such as in proteins, peptides, DNAs carbohydrates, and drugs) allows the biohybrid to be employed in different biological applications, as shown in Figure 5 (Zrazhevskiy and Gao, 2013;Cutler et al, 2013).…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%